Comparison of the mid-term results of complete subtalar release by the Cincinnati and the posteromedial incisions in clubfoot - Karakurt, Lokman; Belhan, Oktay; Varol, Tahir; Yilmaz, Erhan; Serin, Erhan (Turkish Joint Diseases Foundation, 2009)
Objectives: Clinical and radiological results of complete subtalar release operations on idiopathic congenital clubfoot patients were compared for the Cincinati and the posteomedial incisions. Patients and methods: Twenty-six patients (40 feet) that underwent complete subtalar release using the Cincinnati incision (group L 18 patients, 27 feet [12 boys, 6 girls; mean age 7.4 +/- 3.8 month; range 5-24 months]) and posteromedial incision (group 2; 8 patients, 13 feet [6 boys, 2 girls; mean age 10.1 +/- 4.3 month; range 4-16 months]) for idiopathic congenital clubfoot with at least one year follow-up were assessed. Tarsal bone problems, intraoperative and postoperative complications were analyzed separately. Results: According to the Simon's criteria, the clinical results were successful in 27 feet (100%) in group 1 and in I I feet (85%) in group 2 (p>0.05). Radiological results were successful in 16 feet (59%) in group I and in two feet (15%) in group 2 (p<0.05). Superficial skin necrosis occurred in five feet (18.5%) in group I at the early postoperative period and all resolved with conservative treatment. Skin necrosis did not occure in group 2 (p>0.05). The cast was bivalved and opened due to soft tissue swelling at the early postoperative period in 21 feet (77.8%) in group I and only in one foot (7.6%) in group 2 (p<0.05). Conclusion: Posteromedial incision is a suitable and safety incision for complete subtalar release.
Do?uştan çarpık ayaklı olgularda Cincinnati ve posteromedial insizyonlar ile gerçekleştirilen tam subtalar gevşetmenin orta dönem sonuçlarının karşılaştırılması
Keywords: Congenital clubfoot; complete subtalar release; Cincinnati incision; posteromedial incision